Breast Cancer Risk Prevention Model (RICANDRA) to Determine the Risk Factors Associated with the Incidence of Breast Cancer in Women of Childbearing Age in Lampung Province - Aprina, Aprina; Astuti, Titi (Universitas Aisyah Pringsewu, 2022)
Breast cancer in Indonesia is at the top of the list that occurs in women. Most breast cancer conditions are known to be in an advanced stage. Detection at this advanced stage has a very poor prognosis because cancer cells have spread more widely and faster than when cells were detected in an early stage. There was an increase in the number of breast cancer sufferers, both hospitalized and outpatient in RSUDAM. The objectives of this study are to determine the risk factors associated with the incidence of breast cancer in women of childbearing age in Lampung Province and to develop a breast cancer risk prevention model (RICANDRA). This type of research is quantitative with a cross-sectional design. This research was conducted from March to December 2019 in Lampung Province. The target of this study was all women of childbearing age, a sample of 458 women of childbearing age with purposive sampling. The objects taken are advanced age, the first child born at the age of more than 30 years, close family ties/hereditary, history of breast tumor, previous diagnosis, early menstruation, late menopause, use of hormones for menopausal symptoms, exposure to radiation, history of cancer, use of contraceptives hormones, obesity and stress. Collecting data using checklist sheets and questionnaires. Data analysis was univariate, bivariate (chi-square) and multivariate. Research Results: 150 (32.8%) respondents were in the high-risk category and as many as 308 (67.2%) respondents were in the alert category. The results showed that the risk factors that influence breast cancer based on bivariate analysis were advanced age (OR = 5.869; 95% CI: 3.831-8.991; p = 0.000), the first child was born at the age of more than 30 years, close family ties/hereditary, history of breast tumors, Prior diagnosis, Early menstruation, Menopause, Hormone use in menopausal symptoms, Exposure to radiation, had a history of cancer, used hormonal contraception, obesity, stress, smoking, breastfeeding, and alcohol consumption. The most dominant variable affecting the risk factors for breast cancer is the variable exposure to radiation. The magnitude of the risk of breast cancer based on the probability of the logistic function is obtained by the magnitude of the risk of 98.5% WUS experiencing breast cancer and if the risk can be avoided then only 1.5% will experience breast cancer. The Ministry of Health can facilitate regulation on efforts to accelerate efforts to reduce the incidence of breast cancer by making referral designs by strengthening human resources, infrastructure, procedures, or operational methods that can be easily applied to all health workers at the primary level. For women of childbearing age, they must increase their knowledge by participating in activities that can increase knowledge such as mother class activities, and reading or viewing pictures in books, so that WUS knows the risks that may occur in women of childbearing age.